Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I'm new at learning boolean algebra and understand the basic laws. But now I'm trying to proof:

$x'z+ xyz + xy'z = z$

Can someone help me with this please ?

Thanks in advance.

share|cite|improve this question
    
What is this from? What are x' and y' ? Factor out a z from each term on the left and you have reduced your problem to proving x' + xy + xy' =1. – Tom Stephens Aug 13 '10 at 13:15
1  
This is from the boolean algebra. x' and y' are the opposite of x & y. + = OR . = AND – Anonymous Aug 13 '10 at 13:18

Are you still stuck? I'll use your terminology, which seems to be used in electrical engineering.

1) $x'z + xyz + xy'z$

2) $x'z + xz(y+y') $

Since $y+y' = 1$, and $xz1 = xz$ then

3) $x'z + xz$

4) $(x'+x)z$

5) $z$

Hope that helps.

share|cite|improve this answer

If you think of the Boolean operations as complement, intersection and union of sets, which is equivalent since every Boolean algebra is isomorphic to a field of sets, then the equation is obvious.

Namely, on the right side we have the set $z$. On the left side, we have the elements of $z$ separated into three categories: those that are not in $x$, those that are in $x$ and also in $y$, and those that are in $x$ but not in $y$. Since this accounts for all possible elements of $z$, we may deduce the equality.

share|cite|improve this answer

Assuming you mean what is more commonly written as $(\lnot x\land z)\lor(x\land y\land z)\lor(x\land\lnot y\land z)=z$, then it is equivalent, as Tom Stephens points out, to proving that $\lnot x\lor(x\land(y\lor\lnot y))$ is valid (that is, evaluates to true for all x and y). But that's clearly the same as $\lnot x \lor x$.

I used

  • distributivity: $x\lor(y\land z)=(x\lor y)\land(x\lor z)$ and also $x\land(y\lor z)=(x\land y)\lor(x\land z)$
  • excluded middle: $x\lor\lnot x$
share|cite|improve this answer
    
Now I've got this: (I don't know how to make those images like you soz) ||||| x'z + xyz + xy'z = z ||| z[x' + xy + xy'] = z ||| x' + xy + xy' = 1 ||| now the distributivity would be: (x' + x) (x' + y) + xy' = 1 But now I'm stuck here... – Anonymous Aug 13 '10 at 14:08
3  
@user1139: An easy simplification from there: What's (x'+x) ? – Larry Wang Aug 13 '10 at 16:03
    
With your notations I said x'+x(y+y')=x+x'=1. These notations make the law x+yz=(x+y)(x+z) look strange. – rgrig Aug 14 '10 at 6:18

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.